Geographic Information System Implementation Using Google Maps Api In Mapping Muhammadiyah University In Indonesia - Rori Aprisan Ilahi S; Yulia Darmi; Diana Diana; Muhammad Imanullah (Penerbit Jurnal Indonesia, 2023)
Based on data from the PP Muhammadiyah Research and Development Council, there are 62 Muhammadiyah Universities spread throughout Indonesia. Of the many Muhammadiyah Universities it would be very easy if there was a system that could display information and the location of the university in the form of a map. GIS is a computer information system used to process georeferenced spatial data (in the form of details, facts, conditions, etc.) stored in a database. By implementing the Muhammadiyah University Geographic Information System, it is hoped that it can help users in obtaining spatial and non-spatial information about Muhammadiyah University which is spread throughout Indonesia. The system must consist of input and output, therefore the application built consists of an admin section as input and a user as output. The admin application is used to process Muhammadiyah University location data which was built using the PHP programming language and MySQL database. The user application is used for implementing GIS on mapping Muhammadiyah University in Indonesia which runs on the Android operating system and is built using Android Studio with the Java and XML programming languages. The application can display a list of Muhammadiyah University locations in Indonesia in the form of a map and an ordered list. Utilization of google map in the application is to display a map which uses the google map api and displays the route from the user's location to the selected university.